El valor agregado a la materia prima y su fortalecimiento al desarrollo socio económico de los habitantes del cantón Echeandía, provincia Bolívar al 2016 - Montesdeoca Guamán, Christian Hugo (2016)
The purpose of this researching is to provide added value to cacao crops, and its strengthening towards to the socio-economic development of Echeandía canton, 2016 Bolivar province. This researching was conducted through these following objectives, in general “To determine whether if the added cocoa value, allows socio-economic development of agricultural producers from Echeandía City, Bolivar Province . " we identified the following specific objectives: Conduct a situational analysis of Echeandía about cocoa production and its added value; Analyze theoretical aspects of cocoa production, also its value added and socio-economic development; at the end we write a final report according to the interpretation of the results. The fundamental aspect is the design and implement new strategies in order to generate an added value to cocoa production, boosting its development based on their inhabitants needs. The methodology used in this researching project was through the inductive deductive, and analytical methods; the researching types are descriptive, bibliographic and field researching too. The researching sample in this project constitute 16 communities, they are located in the rural Echeandía sector, who they were administered the survey, letting us know that do not give added value to their agricultural production, also training to improve their crops and get over the lack of tranasportation access when they need to sell their product to the wholesale and retail buyers. For the results statistically substantiated form this researching work, its formulation and interpretation, was established as follows: Informative data, Topic, history or state of the art, justification. general objective and three specific objectives, theoretical framework established by conceptual theories, questions to defend, developing questions, methods, researching types, techniques and tools for data collection, samples. For the analysis and interpretation data, a total of 227 surveys were conducted to cocoa producers from Echeandía canton, and it was directed as an observation on their way of working. The research project contains relevant terminology about the problem and its theoretical foundation that takes part of the socio-economic developmen